(untitled) (International Journal of Physiotherapy, 2016)
Background: Focal brain lesions or more small lesions due to stroke can cause measurable damage to cognitive potential. The aim of this paper is to examine the cognitive potential in people who are suffering from a stroke, according to the outcomes of tests of cognitive potential to create and implement somatotherapy and occupational therapy, and after completion of therapy final test of cognitive potential. Methods: A retrospective study was conducted with 64 patients who were suffering from a stroke. The subjects were recommended to somatotherapy and occupational therapy by a physiatrist. Before creating these therapies conducted initial measurement of cognitive potential MoCA test. Score 26-30 points is considered normal, while a score below 26 points indicates the presence of cognitive disorders. For those with a score less than 26 points on the initial examination of the individual created somatotherapy and occupational therapy, as well as for those with a score higher than 26 points to monitor cognitive potential. After the somatotherapy and occupational therapy for a period of 21 days, after 30 minutes during the day, measured the effects of these therapies final testing of cognitive potential MoCA test. Result: On initial examination score <26 points was present in 92.4% of respondents, a score> 26 points was present in 7.8% of respondents, while the final test score of <26 points was present in 78.4% of respondents, while score> 26 points was present in 21.9%. The statistical significance level of p <.005 between the initial and final tests of cognitive potential MoCA test confirmed the Wilcoxon Signed Ranks test, while the statistical significance level of p <.001, confirmed Spearman’s correlation coefficient. Conclusion: This study confirmed the reliability of MoCA test at the initial and final testing the presence of cognitive impairment potential in people with stroke, and reliability is confirmed and when examining the effects of intensive use of individually created somatotherapy and occupational therapy to reduce the damage of cognitive potential. This study confirmed the positive effects of intensive use of individually created somatotherapy and occupational therapy to reduce cognitive impairment potential in people with stroke.